∫ 0 1 x 2 + 2 x cos α + 1 d x
Let α be a constant real number such that the integral above can be expressed as b sin ( c α ) a α , where a , b and c are positive integers with a and b being coprime . Find a + 2 b + 3 c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice solution
Let I = ∫ 0 1 x 2 + 2 x cos α + 1 1 d x
Now, cos 2 α + sin 2 α = 1 . So, I = ∫ 0 1 x 2 + 2 x cos α + cos 2 α + sin 2 α 1 d x = ∫ 0 1 ( x + cos α ) 2 + sin 2 α 1 d x = sin α 1 arctan ( sin α x + cos α ) 0 1 ∵ ∫ ( x + a ) 2 + b 2 d x = b 1 arctan b x + a = sin α 1 ( arctan ( sin α 1 + cos α ) − arctan ( sin α cos α ) ) = sin α 1 ( arctan ( cot 2 α ) − arctan ( cot α ) ) = sin α 1 ( 2 π − 2 α − 2 π + α ) = 2 sin α α
Nice question, having the terms cancel out like that.
I think you should mention that a and b are coprime.
this one is jee style .assume alpha as pi/2 so now integraand turns into 1/(1+x^2).on integrating we get arctanx .substituting limits we get pi/4. now arrange according to given for so on numerator we have pi/2 and in denominator we have [2 times sin(pi/2)]on comparing the coefficient we have a=1 b=2 c=1
Hey! The question is put up to show some specific method for Integrals with Trigonometric Functions. Obviously, most questions have such tricks, which are nothing but the way the human brain thinks.
Problem Loading...
Note Loading...
Set Loading...
\begin{aligned} I & = \int_0^1 \frac{1}{x^2+2x\cos \alpha +1} dx \\ & = \int_0^1 \frac{1}{x^2+2x\cos \alpha + \cos^2 \alpha +1 - \cos^2 \alpha} dx \\ & = \int_0^1 \frac{1}{(x +\cos \alpha)^2 + \sin^2\alpha } dx \\ & = \frac{1}{\sin^2 \alpha} \int_0^1 \frac{1}{\left( \color{#3D99F6} {\frac{x +\cos \alpha}{\sin \alpha}}\right)^2 + 1} dx \quad \quad \small \color{#3D99F6}{\text{Let }\tan \theta = \frac{x +\cos \alpha}{\sin \alpha} \implies \sec^2 \theta \ d\theta = \frac{dx}{\sin \alpha}} \\ & = \frac{\sin \alpha}{\sin^2 \alpha} \int_\color{#3D99F6}{\frac{\pi}{2} - \alpha}^\color{#3D99F6}{\frac{\pi}{2} - \frac{\alpha}{2}} \frac{\sec^2 \theta}{\sec^2 \theta} d\theta \quad \quad \small \color{#3D99F6}{\text{See Note.}} \\ & = \frac{1}{\sin \alpha} \int_{\frac{\pi}{2} - \alpha}^{\frac{\pi}{2} - \frac{\alpha}{2}} \ d\theta \\ & = \frac{1}{\sin \alpha} \left(\frac{\pi}{2}- \frac{\alpha}{2} - \frac{\pi}{2} + \alpha \right) \\ & = \frac{\alpha}{2\sin \alpha} \end{aligned}
⟹ a + 2 b + 3 c = 1 + 2 ( 2 ) + 3 ( 1 ) = 8
Note:
x = 1 ⟹ tan θ ⟹ θ x = 0 ⟹ tan θ ⟹ θ = sin α 1 + cos α = 2 sin 2 α cos 2 α 1 + 2 cos 2 2 α − 1 = cot 2 α = 2 π − 2 α = sin α 0 + cos α = cot α = 2 π − α